Acute gallstone cholecystitis in the elderly: Treatment with emergency ultrasonographic percutaneous cholecystostomy and interval laparoscopic cholecystectomy - Macrì, A.; Scuderi, G.; Saladino, E.; Trimarchi, G.; Terranova, M.; Versaci, A.; Famulari, C. (Surgical endoscopy, 2006)
The treatment of acute cholecystitis in the elderly is still a subject of debate, particularly with reference to the timing of surgery and the role of laparoscopy. From January 1994 to June 2002 we observed 27 patients aged over 70 years with acute calcolous cholecystitis. The patients were submitted to ultrasonographic percutaneous cholecystostomy within 12 h of the acute attack. For two patients (7.4%) at high operative risk, we chose a conservative treatment. Twenty-five patients (92.6%) were submitted, in 15 cases (60%) within 5 days and in 10 patients (40%) within 8 days, to a laparoscopic cholecystectomy. Statistical significance was accepted when the value of p was less than 0.05. Ultrasonographic percutaneous cholecystostomy was performed successfully in all patients, without major morbidity or mortality, and complete resolution of clinical symptoms was obtained within 48 h. The conversion rate of laparoscopy was 20% (13.3% in patients submitted to surgery within 5 days and 30% in the group submitted within 8 days--p > 0.05). The postoperative morbidity rate was 24%; it was higher (40% versus 15%) in patients converted to laparotomy (p > 0.05); mortality was 4%. The period of hospitalization was 11 days in patients operated laparoscopically and 21 days in those converted to open cholecystectomy (p < 0.001). The more rational treatment of acute calcolous cholecystitis in elderly patients is represented by ultrasonographic percutaneous cholecystostomy followed, within 5 days, by laparoscopic cholecystectomy using an abdominal insufflation maximum to 12 mmHg and a limited 10-15 degrees head-up tilt.